Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Web Pada Paud Qur’an Nurul Ikhlas Cipayung - Muhamad Ardy Kurniawan; Muhammad Arrasyid; Nurhaliza Arfadilla; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
In general, the registration process for new students is carried out through the stages of registration and announcement of student acceptance. In this study its application to PAUD QUR'AN NURUL IKHLAS CIPAYUNG, which so far is still in the process of admitting new students manually. This will certainly complicate the process of data collection, administration and information as well as less efficient use of time, place, cost and manpower. For this reason, an information system is needed that can assist in a more accurate and efficient process of admitting new students. The research method used is observation and literature study. The research method uses the PHP programming language and MySQL database. This research resulted in an efficient and effective New Student Registration Information System at the web-based PAUD QUR'AN NURUL IKHLAS CIPAYUNG which is capable of managing the registration process for new students, namely registration and reports of new students.